2016
DOI: 10.1002/sam.11313
|View full text |Cite
|
Sign up to set email alerts
|

Fast robust SUR with economical and actuarial applications

Abstract: The seemingly unrelated regression (SUR) model is a generalization of a linear regression model consisting of more than one equation, where the error terms of these equations are contemporaneously correlated. The standard feasible generalized linear squares (FGLS) estimator is efficient as it takes into account the covariance structure of the errors, but it is also very sensitive to outliers. The robust SUR estimator of Bilodeau and Duchesne (Canadian Journal of Statistics, 28:277-288, 2000) can accommodate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Several robust alternatives have already been developed in the univariate claims reserving framework (see e.g., Brazauskas et al (2009) 2017)). Hubert et al (2017) have shown that FGLS estimators in the GMCL model are also very sensitive to outliers. Please note that the multivariate aspect makes the task of outlier detection more challenging because outliers can be univariate or multivariate.…”
Section: Robust Gmcl Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several robust alternatives have already been developed in the univariate claims reserving framework (see e.g., Brazauskas et al (2009) 2017)). Hubert et al (2017) have shown that FGLS estimators in the GMCL model are also very sensitive to outliers. Please note that the multivariate aspect makes the task of outlier detection more challenging because outliers can be univariate or multivariate.…”
Section: Robust Gmcl Methodsmentioning
confidence: 99%
“…Therefore, highly robust S-estimators are computed to obtain a highly robust scale estimator. S-estimators have been introduced for SUR models in Bilodeau and Duchesne (2000), and a computational efficient algorithm has been proposed in Hubert et al (2017). Robustness can be measured by the breakdown point of an estimator, which is roughly equal to the maximal fraction of contaminated observations that an estimator can tolerate before its bias becomes unbounded.…”
Section: Robust Gmcl Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In insurance applications, normality assumptions may be misleading as a measure of dependency in the tails of the variables. The impact of loss triangle dependence on risk margins was also considered by Hubert et al (2017), who proposed the FastSUR algorithm, in order to robustify the general multivariate Chain Ladder method of Zhang (2010), where the parameters were estimated using seemingly unrelated regression(SUR). Based on MM-estimators, Peremans et al (2018) proposed a robust alternative that estimates the SUR parameters in a more outlier resistant way.…”
Section: Correlation Between Claims Reserving Trianglesmentioning
confidence: 99%
“…Bilodeau and Duchesne (2000) have introduced robust and affine equivariant S-estimators. Recently, Hubert et al (2017) developed an efficient algorithm for these estimators. Despite its remarkable robustness properties, S-estimators can have a low efficiency, which makes them less suitable for inference.…”
Section: Introductionmentioning
confidence: 99%